Analisis Pengaruh Variasi Kecepatan Putaran Pisau Terhadap Kualitas Potongan Bawang Merah Pada Mesin Pengiris - Muhammad Dava Faruqi; Mhd. Taufik Ardaha; Tino Hermanto; Yopan Rahmad Aldori (CV. IRA PUBLISHING, 2025)
Manually slicing shallots is challenging for MSMEs engaged in the fried shallot industry. This study aims to analyze the effect of variations in the speed of knife rotation on the quality of the results of the sliced ​​shallots on the slicing machine. The study was conducted experimentally with five variations in rotation speed, measured using a tachometer, and visual observation to assess the quality of the slices. The results showed that the cutting speed increased from 61 kg/hour to 89 kg/hour, with the quality of the slices remaining at 85%. This study recommends the highest speed as optimal for productivity without reducing the quality of the slices.